Genome-Wide, Integrative Analysis Implicates Exosome-Derived MicroRNA Dysregulation in Schizophrenia. (16th February 2019) - Du, Yang; Yu, Yun; Hu, Yang; Li, Xiao-Wan; Wei, Ze-Xu; Pan, Rui-Yuan; Li, Xue-Song; Zheng, Guang-En; Qin, Xiao-Yan; Liu, Qing-Shan; Cheng, Yong
Abstract: Genetic variants conferring risk for schizophrenia (SCZ) have been extensively studied, but the role of posttranscriptional mechanisms in SCZ is not well studied. Here we performed the first genome-wide microRNA (miRNA) expression profiling in serum-derived exosome from 49 first-episode, drug-free SCZ patients and 46 controls and identified miRNAs and co-regulated modules that were perturbed in SCZ. Putative targets of these SCZ-affected miRNAs were enriched strongly for genes that have been implicated in protein glycosylation and were also related to neurotransmitter receptor and dendrite (spine) development. We validated several differentially expressed blood exosomal miRNAs in 100 SCZ patients as compared with 100 controls by quantitative reverse transcription-polymerase chain reaction. The potential regulatory relationships between several SCZ-affected miRNAs and their putative target genes were also validated. These include hsa-miR-206, which is the most upregulated miRNA in the blood exosomes of SCZ patients and that previously reported to regulate brain-derived neurotrophic factor expression, which we showed reduced mRNA and protein levels in the blood of SCZ patients. In addition, we found 11 miRNAs in blood exosomes from the miRNA sequence data that can be used to classify samples from SCZ patients and control subjects with close to 90% accuracy in the training samples, and approximately 75% accuracy in the testing samples. Our findings support a role for exosomal miRNA dysregulation in SCZ pathophysiology and provide a rich data set and framework for future analyses of miRNAs in the disease, and our data also suggest that blood exosomal miRNAs are promising biomarkers for SCZ.